Lactiplantibacillus plantarum improves the growth performance and meat quality of broilers by regulating the cecal microbiota and metabolites - Liu, Yu; Wang, Zhisheng; Xi, Wenshuo; Yuan, Junmeng; Zhang, Kai; Liu, Huawei; Zhao, Jinshan; Wang, Yang (Frontiers in Microbiology, 2025)
Gut microbiota can digest and ferment feed into metabolites to influence the meat quality. Probiotics are used to regulate the gut microbiota. In this study, a total of 360 broilers were assigned to 4 treatments (10 broilers per cage): control (Con), low dose of Lactiplantibacillus plantarum HW1 (Lp_L), medium dose of Lp (Lp_M) and high dose of Lp (Lp_H) for a 42-day experimental period. Results showed that the Lp treatments improved the growth performance, carcass traits, breast meat quality, and also influenced the fatty acids composition, including the decrease of n-6PUFA/n-3PUFA, and the increase of C18:3n3, ∑n-3PUFA and PUFA/SFA. The lipid metabolism-related gene expressions in the liver showed that Lp treatments increased the expression of AMPK, CPT-1α, PPARα, ATGL and also decreased the expression of PPARγ, SREBP-1c, ACC, FAS, LPL, and SCD. Moreover, the abundances of gut microbiota, such as Synergistaceae and Synergistes were influenced by the Lp treatments. Functional prediction of the gut microbiota indicated that pathways, including pancreatic secretion and spliceosome were enriched by the Lp treatments. Untargeted metabolomics revealed that the Lp treatments altered the content of metabolites, such as 6-ketomyristic acid and indole-3-acetamide. These metabolites were enriched in pathways including fatty acid metabolism. Correlation analyses revealed potential interactions between growth performance and meat quality, as well as gut microbiota (Synergistes, etc.) and metabolites (6-ketomyristic acid, etc.). Overall, our data show that the Lp treatments significantly improved the growth performance, carcass traits and meat quality of broilers by regulating fatty acids, gut microbiota and metabolites.